2019
DOI: 10.1261/rna.073304.119
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of IFIT1 and IFIT5 interactions with different native and engineered RNAs and its consequences for designing mRNA-based therapeutics

Abstract: In response to foreign RNA, cellular antiviral mechanisms stimulate high expression of interferon-induced proteins with tetratricopeptide repeats (IFITs). Two members of the IFIT protein family, IFIT1 and IFIT5, are capable of binding the very terminal 5 ′ ′ ′ ′ ′ end of mRNA. In eukaryotes, these mRNA termini contain a cap structure (m 7 GpppN, cap 0) that is often subjected to further modifications. Here, we performed a thorough examination of IFIT1 and IFIT5 binding to a wide spectrum of differently capped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…The discovery of diverse modifications in endogenous mRNA caps has provided versatility to mRNA function, and because the cap structure helps distinguish endogenous mRNAs from viral RNAs, the 5 0 termini of synthetic mRNAs are routinely modified to recapitulate these endogenous structures [14,15]. The biological significance of the 5 0 cap variations is routinely evaluated using in vitro-synthesized RNA in either cell-based or biochemical assays to understand the effects of the modifications in enhancing translation and evading immune responses [25,88,97,98]. There are some considerations that should be taken into account when utilizing cell-based assays in combination with synthetic modified mRNAs.…”
Section: Mrna Termini Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of diverse modifications in endogenous mRNA caps has provided versatility to mRNA function, and because the cap structure helps distinguish endogenous mRNAs from viral RNAs, the 5 0 termini of synthetic mRNAs are routinely modified to recapitulate these endogenous structures [14,15]. The biological significance of the 5 0 cap variations is routinely evaluated using in vitro-synthesized RNA in either cell-based or biochemical assays to understand the effects of the modifications in enhancing translation and evading immune responses [25,88,97,98]. There are some considerations that should be taken into account when utilizing cell-based assays in combination with synthetic modified mRNAs.…”
Section: Mrna Termini Modificationsmentioning
confidence: 99%
“…Biophysical assays allowing direct mRNA-protein binding have also been used in combination with cell-based assays. Binding of the 5 0 ends of mRNA with either the cap-binding protein eIF4E, the cytosolic receptors (IFIT1), or the decapping enzyme (DcpS) has been evaluated to determine the kinetics of these interactions and deduce a role of the 5 0 cap modification [25,97].…”
Section: Mrna Termini Modificationsmentioning
confidence: 99%
“…using the primer extension method calculated it as 372 (±21) nM. More recent studies by Miedziak et al showed that the binding affinity of IFIT5 with pppRNA is equal to 42.7 (±1.6) or 113 (±12) nM depending on the presence of the magnesium cation, whereas binding to GpppRNA or m 7 GpppRNA is weak (Table ). Seeing inaccuracy in experimental results, we decided to try another method to estimate binding affinity: microscale thermophoresis (MST).…”
Section: Resultsmentioning
confidence: 99%
“… a Abbas et al, Method pulldown, buffer 50 mM Tris, pH 7.5, 100 mM NaCl, 5% (v/v) glycerol, 0.2% (v/v) Nonidet-P40, 1.5 mM MgCl 2 , pppRNA7SK-as 378 nt (with GAA as the first three nucleotides). For this column, the effect of particular mutations on binding affinity is described. b Katibah et al., Method EMSA, buffer 20 mM Tris·HCl, pH 8.0, 200 mM NaCl, 5 mM MgCl 2 , 10% (v/v) glycerol, 2 mM DTT, and 0.1 mg/mL BSA, pppRNA WNV 30nt (with AGU as the first three nucleotides). c Abbas et al, Method EMSA, buffer 10 mM Tris pH 7.9, 100 mM NaCl, 1 mM TCEP, 5% v/v glycerol, pppRNA 44nt (with GGG as the first three nucleotides). d Kumar et al, Method Primer extension, buffer 20 mM Tris, pH 7.5, 100 mM KCl, 2.5 mM MgCl 2 , 1 mM ATP, 0.2 mM GTP, 1 mM DTT and 0.25 mM spermidine, pppRNA β-globin (with GAC as the first three nucleotides). e Miedziak et al., Method Biolayer Interferometry, buffer 50 mM phosphate buffer pH 7.2, 150 mM NaCl, 10% glycerol, 0.5 mM DTT, 0.1% BSA, and 0.05% Tween 20, pppRNA 16nt (with GGG as the first three nucleotides). f Our experiment, Method microscale thermophoresis, PBS, 5% glycerol, 0.5 mM TCEP, 0.05% Tween20, 1 mM MgCl2, pppRNA-cy5 12nt (with AAA as the first three nucleotides). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation